N-Heterocyclic carbene catalyzed oxidative stannylation of aldehydes: a facile entry to organotin(IV) carboxylates - Reddi, Rambabu N.; Malekar, Pushpa V.; Sudalai, Arumugam (Tetrahedron Letters, 2013)
A simple protocol is described for the oxidative transformation of aldehydes to the corresponding organotin(IV) carboxylates in high yields (up to 90%) that utilizes atmospheric O-2 as the sole oxidant, N-heterocyclic carbene as catalyst (at 10 mol %), and tributyl tin chloride as stannylating agent. The uniqueness of the reaction lies in the direct conversion of aldehydes to the corresponding organotin(IV) carboxylates via stannylation of carboxylic acids, generated from the reaction of a Breslow intermediate with O-2. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Carboxylic acid stannanes; N-Heterocyclic carbene; Oxidative stannylation; oxygen; Tributyltin chloride

N-heterocyclic carbene (NHC)-catalyzed transformations for the synthesis of heterocycles - Das, Tamal Kanti; Biju, Akkattu T. (Progress in Heterocyclic Chemistry, 2020)
N-heterocyclic carbene (NHC)-based organocatalysis has been widely used for unconventional access to various target molecules. The use of chiral NHCs in the process results in the enantioselective synthesis of various heterocycles. The underlying principle of many of the NHC-catalyzed reactions is the remarkable ability of NHCs to reverse the normal mode of reactivity of aldehydes (umpolung). NHCs can catalyze transformations proceeding via the umpolung or nonumpolung mode for the synthesis of various functionalized molecules. The recent advances in the application of NHCs for the synthesis of various heterocyclic compounds are highlighted in this chapter.
Keywords: aldehyde umpolung; Aldimine umpolung; benzoin reaction; Breslow intermediates; Enantioselective synthesis; Heterocyclic synthesis; N-Heterocyclic carbene; Stetter reaction

Enhancing diradical character of chichibabin's hydrocarbon through fluoride substitution - Kundu, Gargi; Dash, Soumya Ranjan; Kumar, Ravi; Vanka, Kumar; Ghosh, Aryya; Sen, Sakya S. (ChemPlusChem, 2023)
In this work, 5-SIDipp [SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] (1) derived Chichibabin's hydrocarbon with an octafluorobiphenylene spacer (3) has been reported. The addition of two equivalents of 5-SIDipp with decafluorobiphenyl in presence of BF3 gives the double C-F bond activated imidazolium salt with two tetrafluoroborate anions, 2. Further reduction of 2 gives the fluorine substituted 5-SIDipp based Chichibabin's hydrocarbon, 3. Quantum chemical calculations suggested a singlet state of 3 with a singlet-triplet energy gap (?ES-T) of 3.7 kcal mol(-1), which is substantially lower with respect to the hydrogen substituted NHC-based Chichibabin's hydrocarbons (10.7 kcal mol(-1), B3LYP). As a result, the diradical character (y) of 3 (y=0.62) is also noticeably higher than the hydrogen substituted CHs (y=0.41-0.43). The ?ES-T was found to be higher in CASSCF (22.24 kcal mol(-1)) and CASPT2 (11.17 kcal mol(-1)) for 3 and the diradical character (d) is 44.6 %.
Keywords: C-F Bond Activation; Chichibabin & PRIME; DFT; N-Heterocyclic carbene; s Hydrocarbon

Access to NHC-Boryl mono- and bis-selenide and utility as mild selenium transfer reagent including to the C-F bond - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (Chemistry- a european journal, 2024)
Reactions of 5-SIDipp & sdot; BH3 (5-SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene) (1) with diphenyldiselenide provide access to 5-SIDipp-boryl mono- (5-SIDipp & sdot; BH2SePh) (2) and bis-selenide (5-SIDipp & sdot; BH(SePh)2) (3). The facile cleavage of the B-Se bond makes 2 a neutral source of selenium nucleophiles in substitutions reactions with benzyl bromides, and provide access to the corresponding selenoethers. The direct transformations of one of the C(sp2)-F bonds of C5F5N and C6F5CF3 to C-Se bonds have also been achieved by the use of 2 without employing transition-metal catalysts. While it was previously established that C6F6 could undergo complete defluoroselenation under harsh conditions, we successfully achieved partial defluorination of C6F6 by employing 2 as a mild selenide transfer reagent. During the formation of C-Se bonds through the cleavage of C-F bonds, the potential by-product NHC & sdot; BH2F undergoes ring expansion of the NHC, leading to the formation of the six-membered diaazafluoroborinane (7). Access to NHC & sdot; boryl mono- and bis-selenides from NHC & sdot; BH3 has been achieved. The boryl mono selenide has been demonstrated to function as a selenium transfer reagent, enabling the synthesis of selenoethers from benzyl bromide. Additionally, it can also facilitate the conversion of the challenging aromatic C-F bond to a C-Se bond, resulting in concomitant ring expansion of NHC & sdot; haloborane.image
Keywords: boron; C-F Bond Activation; N-Heterocyclic carbene; Ring expansion; Selenium